Mobilisasi Politik Anggota XTC Indonesia Terhadap Pasangan Calon Rindu Pada Pemilihan Gubernur Jawa Barat Tahun 2018 - Ginar Maulana; Widya Setiabudi Sumadinata; Yusa Djuyandi (Mahesa Research Center, 2021)
This paper aims to examine and understand the form of political mobilization and also the reason of the XTC Indonesia Community Organization in supporting the spouses of candidates Ridwan Kamil and Uu Ruzhanul Ulum in the West Java Governor Election in 2018. This research method uses qualitative approach, data and information obtained through observation method, interview and library method (Library Research). The results of the study concluded that, political mobilization carried out by XTC Indonesia is a gathering of members / cadres who are carried out through a command to be collected, and involved in democratic parties through political participation by mobilizing its members to support the spouse of Ridwan Kamil - Uu Ruzhanul Ulum in the West Java Governor Election Year 2018.